Distributed optimal in-network resource allocation algorithm design via a control theoretic approach - Kia, Solmaz S. (Systems & control letters, 2017)
In this paper, we consider an in-network optimal resource allocation problem with multiple demand equations. We propose a novel distributed continuous-time algorithm that solves the problem over strongly connected and weight-balanced digraph network topologies when the local cost functions are strongly convex. We also discuss the extension of our convergence guarantees to dynamically changing topologies. Finally, we show that if the network is an undirected connected graph, we can guarantee stability and convergence of our algorithm for problems involving local convex functions. This convergence guarantee is to a point in the set of minimizers of our optimal resource allocation problem. The design and analysis of our algorithm are carried out using a control theoretic approach. We demonstrate our results through a numerical example.